2021
DOI: 10.1530/ec-20-0648
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate thyroid cytology: detecting malignancy using analysis of nuclear images

Abstract: Background: Thyroid nodules diagnosed as “Atypia of Undetermined Significance/Follicular Lesion of Undetermined Significance” (AUS/FLUS) or “Follicular Neoplasm/Suspected Follicular Neoplasm” (FN/SFN)”, according to Bethesda's classification, represent a challenge in clinical practice. Computerized analysis of nuclear images (CANI) could be a useful tool for these cases. Our aim was to evaluate the ability of CANI to correctly classify AUS/FLUS and FN/SFN thyroid nodules for malignancy. Methods: We studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…We demonstrated the importance of evaluating nuclear parameters using digital pathology, consistent with the findings of studies analysing follicular cells in cytological 9–11,14 and histological 15–17 samples. Studies with histological samples are more common in the literature 15–17 .…”
Section: Discussion/conclusionsupporting
confidence: 85%
See 3 more Smart Citations
“…We demonstrated the importance of evaluating nuclear parameters using digital pathology, consistent with the findings of studies analysing follicular cells in cytological 9–11,14 and histological 15–17 samples. Studies with histological samples are more common in the literature 15–17 .…”
Section: Discussion/conclusionsupporting
confidence: 85%
“…This is consistent with the concept of nuclear size as an important feature for discriminating benign from malignant cells. 13 We demonstrated the importance of evaluating nuclear parameters using digital pathology, consistent with the findings of studies analysing follicular cells in cytological [9][10][11]14 and histological [15][16][17] samples. Studies with histological samples are more common in the literature.…”
Section: Ta B L Esupporting
confidence: 83%
See 2 more Smart Citations
“…Wide variation of AUS was seen since 42% physicians received benign histo diagnosis after surgery, and 74% received malignant histologic [14] Other modalities such as Computerized analysis of nuclear images (CANI) also reported beneficial in AUS case. Hayashi et al [17] reported sensitivity and specificity in detecting malignancy that higher than 80% of AUS cases with CANI [17].…”
Section: Discussionmentioning
confidence: 99%